Fat and fat‐free mass measurement agreement by dual‐energy X‐ray absorptiometry versus bioelectrical impedance analysis: Effects of posture and waist circumference - Katie M. Ellison; Sarah E. Ehrlicher; Aseel El Zein; R. Drew Sayer (Wiley, 2024)
Abstract Background Bioelectrical impedance analysis (BIA) operates under the assumption that the conductor has a uniform cylindrical shape. However, this assumption may be violated if measures are taken in the seated position, especially in people with a high waist circumference (WC). Aims The aims of this research were to determine whether posture (supine, standing, and seated) and WC affect agreement between BIA and dual‐energy X‐ray absorptiometry (DXA) measures of fat mass (FM) and fat‐free mass (FFM). Materials & Methods Baseline data were collected from 28 adults (mean = 61.4 ± 6.9 years, 64.3% female) with obesity (BMI 38.6 ± 5.0 kg/m2). Body composition was measured using BIA in the supine, standing, and seated positions and by DXA while supine. Intraclass correlation coefficient (ICC) analyses with two‐way mixed effects and absolute agreement were performed to determine agreement. Results Point estimates were excellent for FM and FFM while supine, excellent for FM and good for FFM while standing, and moderate for FM and good for FFM while seated. BIA measures in the supine position resulted in the narrowest 95% confidence intervals compared with other positions. Better agreement was observed across all positions in participants with a WC below the median (118.3 cm). Discussion Despite the potential pragmatic value of measuring with BIA in a seated position, the results of this analysis demonstrate the poorest agreement between DXA and BIA methods, especially in individuals with high WC. Conclusion Findings from this study demonstrate that BIA, particularly when measured in a supine position, can serve as a viable alternative to DXA for measuring body composition in people with obesity.